THE USE OF AUDIO VISUAL TO IMPROVE LISTENING - Mimi Kirana (Universitas Syiah Kuala, 2016)
The increasing of globalization, pushes people to be fluent in some foreign language, one of which is English. This research is to: (a) describe a strategy of teaching English using an Audio Visual Method (AVM), and (b) to compare the results from an experimental group (EG) of students learning listening comprehension using the AVM and a control group (CG) using a standard method. This research, was done at SMP Negeri 15 Lamjame, Banda Aceh. The findings showed that the students in the EG got significantly higher average scores (69) for listening comprehension. than those from the CG (62). The t–test result showed that the listening ability of the students from the two groups was significantly different. Thus, it can be concluded that the students taught using the AVM got better results in listening comprehension than students who were taught using the standard listening comprehension technique.